Community-Based Disaster Risk Management in Azerbaijan - Abbasov, Rovshan (SpringerBriefs in Geography,, 2018)
This book illustrates the main factors of vulnerability and gives a clear picture about the possible interventions to reduce disaster risks both in schools and communities in Azerbaijan. A new methodology for child centered vulnerability assessments both on school and community levels has been developed. This methodology can be used to assess the level of vulnerability of schools and communities. The book is a newly prepared training manual which will help practitioners conduct trainings for government and community organizations. While the book is focused on a specific region, the suggested approach is generic and can be used elsewhere.